Profile of Dermatologic Emergencies At The Emergency Department of RSUD Jombang: A Three-Year Retrospective Study (2023 To 2025) - Ruri Wahyu Lestanto; Andri Catur Jatmiko (CV. Inara, 2026)
Dermatologic emergencies comprise acute skin conditions requiring prompt recognition and management because delayed treatment may result in systemic complications or death. Epidemiological data from regional hospitals in Indonesia remain limited. To describe the profile of dermatologic emergencies at the Emergency Department of RSUD Jombang during 2023–2025. A retrospective descriptive study was conducted using medical records of dermatology and venereology patients admitted through the emergency department and hospitalized under dermatology specialists. Total sampling was applied. Variables included demographic characteristics, diagnosis, emergency category, length of stay, and patient outcomes. A total of 216 cases were analyzed. Most patients were male (54.6%), with a mean age of 51.6 years; the largest age group was 40–59 years (43.5%). Drug reactions or eruptions (27.8%), dermatitis or eczema (22.7%), leprosy reactions (15.7%), and infections (15.3%) were the most common diagnostic categories. Erythroderma (19.9%), leprosy reaction (15.3%), and Stevens–Johnson syndrome (11.6%) were the leading diagnoses. Most cases were classified as urgent (64.8%), and 88.9% of patients showed clinical improvement. Drug reactions, erythroderma, and leprosy-related conditions predominated among dermatologic emergencies, providing evidence to strengthen emergency preparedness and acute dermatology services in regional hospitals.